Quantum key distribution in real life - Ali, Sellami; Ahmed, Abdallah Hassen; Habaebi, Mohamed Hadi; Chowdhury, Md. Sazzad Hossien (IDOSI Publication, 2012)
The quantum key distribution (QKD) technique establishes secret keys shared between two communicating parties. Theoretically, unconditional security provided by QKD is guaranteed by the fundamental laws of quantum physics. in the real life, it is still possible to obtain unconditionally secure QKD, even with (phase randomized) attenuated laser pulses, as theoretically demonstrated by Gottesman-Lo-L¨utkenhaus-Preskill (GLLP). However, one must pay a steep price by placing severe limits on the distance and the key generation rate. These problems were solved using the decoy state method introduced by Hwang. In this paper, we have proposed a method to estimate parameters of the decoy state method based on two decoy state protocol for both BB84 and SARG04. The vacuum and weak decoy state protocol has been introduced as a special case of two decoy states protocol. This method has given different lower bound of the fraction of single-photon counts (y1), the fraction of two-photon counts (y2), the upper bound QBER of single-photon pulses (e1), the upper bound QBER of two-photon pulses (e2) and the lower bound of key generation rate for both BB84 and SARG04. The fiber based QKD systems also have been simulated using the proposed method for BB84 and SARG04. The numerical simulation has shown that the fiber based QKD systems using the proposed method for BB84 are able to achieve both a higher secret key rate and greater secure distance than that of SARG04. Key words: Quantum cryptography % Quantum key distribution % Decoy state protocol and optical communications